PENINGKATAN KOMUNIKASI INTERPERSONAL MELALUI KONSELING PERSONAL CENTERED TEKNIK REFLECTION OF THOUGHTS AND FEELINGS - Fasya, Andien Aulia Mufida; Mahmudi, Ibnu; Kadafi, Asroful (Universitas Muria Kudus, 2024)
Interpersonal communication is an important source for expressing oneself to build, improve and maintain good relationships with other people. Low interpersonal communication problems cause students to be individualistic, namely students who are less open in speaking, less empathetic, less supportive and upholding equality. Starting from this problem. The researcher formulated the aim of this research as to improve students' interpersonal communication through group counseling and using a personal centered counseling approach, the Reflection of Thoughts and Feelings technique. This research uses a one group pre-test and post-test experimental research design. This research used a population of 34 students and a research sample of 7 students. The data analysis technique uses the Wilcoxon test. After carrying out the pre-test and post-test, 2 students (28.57%) had a high level of interpersonal communication and 5 students (71.43%) had a moderate level of communication. Based on the research results, it shows that personal centered counseling, the Reflection of Thoughts and Feelings technique, is effective for improving students' interpersonal communication